Screening study for antibacterial activity from Marine and freshwater microalgae - CORONA, E.; FERNANDEZ-ACERO, J.; BARTUAL, A. (International Journal of Pharma and Bio Sciences, 2017)
Nowadays, several pathogenic bacteria present resistance against common antibiotics, being necessary the search new drugs with activity against resistant pathogens. The capacity of microalgae to produce diverse secondary metabolites has been widely reported. Here we searched the antibacterial activity of several organic extracts from different microalgae. We used five marine diatoms and a consortium of freshwater Chlorophyceae obtained from urban wastewater treatment. Target organisms were both Gram-negative (Pseudomonas fluorescens, Serratia marcescens and Escherichia coli) and Gram-positive (Micrococcus luteus, Bacillus subtilis and Staphylococcus epidermidis) human pathogenic bacterial strains. Antibacterial activity was evaluated by agar diffusion assays. P. fluorescens, S. marcescens and S. epidermidis were inhibited by many of the extracts tested, while E. coli, M. luteus and B. subtilis were found completely resistant. These results corroborate the potential use of microalgae extracts as a source of new antibiotic compound and open the possibility of use of wastewater cultured algae.